The Immediate Threat to our Oceans - Vopel, K (APN Holdings NZ Limited, 2010)
"We are about to fundamentally change the chemistry of our ocean. The greatest risk to our marine environment is the accelerating enrichment of seawater with anthropogenic CO2. This CO2 pollution results from our ignorance of the fundamental processes that link the marine environment with the atmosphere and the land. The overall human CO2 emissions over the industrial era amount to close to 560 billion tons. A little less than half of this CO2 remains in the atmosphere acting as greenhouse gas leading to climate change. The remainder is, at present, removed in roughly equal parts into the ocean and by land vegetation. We are emitting roughly 10 billion tons of carbon annually, a rate that exceeds the natural emissions by a factor of nearly 100. About 87% of this release originates from fossil fuel combustion and cement production and another 12% from deforestation. The ocean is a complex system well designed for maintaining a balance between inputs and outputs of carbon but the current rapid rise in atmospheric CO2 exceeds its capacity to maintain this balance.